Disease Course in Patients Switched from Natalizumab to Alemtuzumab: An Italian Multicenter, Prospective, Observational Study - Simona Malucchi; Paola Perini; Francesca Rinaldi; Marta Radaelli; Maria Malentacchi; Antonio Bertolotto; Alessia Di Sapio (Neurology and Therapy)
Abstract Introduction Natalizumab is a highly efficacious therapy (HET) for patients with relapsing remitting multiple sclerosis (RRMS). Its prolonged use is limited by the risk of progressive multifocal leukoencephalopathy (PML) in patients positive for anti-JCV antibodies. Aims of this work were to evaluate clinical and radiological efficacy at 6 and 12 months after alemtuzumab infusion in patients switching from natalizumab and the safety of this exit strategy. Methods This real-world, prospective, multicentric, observational study was conducted in three Italian MS centers and included a total of 35 patients with RRMS. Natalizumab treatment occurred from October 2010 to April 2021, whereas switch to alemtuzumab occurred from February 2018 to January 2023. Median washout period between the two drugs was 2 months. Patients underwent brain MRI before alemtuzumab start and then 6 and 12 months after the first alemtuzumab cycle. Results No clinical relapse occurred during the washout period, nor between the first and second alemtuzumab infusion. Radiological activity was present in 4/35 (11%) and 2/35 (6%) patients, respectively, at 6 and 12 months after the first alemtuzumab administration. Expanded Disability Status Scale (EDSS) increase developed in 4/35 (11%) and 5/35 patients (14%), respectively, at 6 and 12 months. No PML occurred, nor any serious adverse event. For patients in center 1 (17 patients), follow-up continued for a median of 3.5 years; NEDA-3 (No Evidence of Disease Activity) was present in 14/17 patients (82%) at the end of follow-up. Autoimmunity occurred in 23% of patients. Conclusions Alemtuzumab is a valid exit strategy after natalizumab interruption.